Preparation method of carbon-coated graphite composite material, carbon-coated graphite composite material and battery negative electrode

By using carbon coating technology on graphite materials, using sugars and non-carbon heteroatom-containing compounds as carbon sources, combined with the synergistic effect of surfactants, uniform coating of graphite materials was successfully achieved, solving the problem of collapse of graphite negative electrode materials during circulation, and significantly improving the rate performance and cycle life of the battery.

CN119517950AActive Publication Date: 2025-02-25TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202311087894.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

Graphite negative electrode material is prone to collapse during the charge and discharge cycle, resulting in a decrease in the specific capacity of the battery and a shortened energy storage life, and poor rate performance, which cannot meet the development needs of power batteries and energy storage batteries.

Method used

By mixing and processing the alkaline mixture of graphite materials, sugars as main carbon sources, compounds containing non-carbon heteroatoms as synergistic carbon sources and surfactants as auxiliary agents, a dispersion liquid is obtained, and a carbon-coated graphite composite material is formed in drying, coking and carbonization treatments.

Benefits of technology

The graphite material is uniformly and completely coated with carbon, preventing the merger and agglomeration of graphite particles, improving the electrochemical reversible capacity and cycling performance of the material, and significantly improving the rate performance and cycle life of the negative electrode of the lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517950A_ABST
    Figure CN119517950A_ABST
Patent Text Reader

Abstract

The invention belongs to the related technical field of carbon materials and batteries, and particularly relates to a preparation method of a carbon-coated graphite composite material, the carbon-coated graphite composite material and a battery negative electrode. A preparation method of a carbon-coated graphite composite material comprises the following steps: mixing an alkaline mixed solution containing a graphite material, a main carbon source for coating, a synergistic carbon source for coating and an auxiliary agent to obtain a dispersion liquid; performing drying and coking treatment on the dispersion liquid under a preset condition to form a carbon-coated graphite precursor; carrying out carbonization treatment on the carbon-coated graphite precursor under a protective gas environment condition to obtain a carbon-coated graphite composite material; the main carbon source for coating comprises saccharides; the synergistic carbon source for coating comprises a compound containing non-carbon heteroatoms; and the auxiliary agent comprises a surfactant, can be in synergistic effect with the synergistic carbon source for coating, and can fully disperse the alkaline mixed solution to obtain a uniformly distributed dispersion solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of carbon materials and batteries, and in particular to a method for preparing a carbon-coated graphite composite material, a carbon-coated graphite composite material and a battery negative electrode. Background Art

[0002] Lithium-ion batteries are now widely used in various electrical equipment, and related technologies and industries have achieved rapid development. Application scenarios such as electric vehicles and electrochemical energy storage have put forward increasingly higher requirements on the performance of lithium-ion batteries, especially in terms of high safety, high power, and long life.

[0003] Graphite is widely used as the negative electrode material of lithium-ion batteries, with advantages such as low working potential, long cycle life and relatively low cost. However, the graphite layered structure has poor stability and is prone to collapse after a long period of charge and discharge cycles, resulting in a serious decrease in battery specific capacity and a significant shortening of energy storage life. In addition, the rate performance of graphite negative electrodes is poor, and it cannot be charged and discharged with large currents, which does not meet the development needs of power batteries and frequency modulation energy storage. Therefore, graphite materials need to be effectively modified to become negative electrode materials for high-performance power batteries and energy storage batteries.

[0004] Surface modification by coating with ultra-thin carbon layers is an effective way to improve the electrochemical performance of graphite. It can modify the defects of graphite materials such as holes, grooves, cracks, etc., optimize the solid electrolyte layer formed at the interface, prevent the co-embedding of electrolyte, effectively prevent the peeling and pulverization of the graphite layer during the charge and discharge process, and improve the electrochemical reversible capacity and cycle performance of the material. Currently, the most commonly used coating methods are mainly solid-phase or liquid-phase coating of asphalt, which has the disadvantages of uneven coating and poor coating effect. Summary of the invention

[0005] The embodiments of the present application provide a method for preparing a carbon-coated graphite composite material, a carbon-coated graphite composite material and a battery negative electrode, which can make carbon uniformly and completely coat a graphite material.

[0006] In a first aspect, an embodiment of the present application provides a method for preparing a carbon-coated graphite composite material, comprising:

[0007] The alkaline mixed solution containing the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the auxiliary agent is mixed to obtain a dispersion;

[0008] Drying and coking the dispersion under preset conditions to form a carbon-coated graphite precursor;

[0009] Carbonizing the carbon-coated graphite precursor under protective gas environment conditions to obtain a carbon-coated graphite composite material;

[0010] The main carbon source for coating includes sugars;

[0011] The synergistic carbon source for coating includes a compound containing non-carbon heteroatoms;

[0012] The auxiliary agent includes a surfactant, which can cooperate with the synergistic carbon source for coating and can fully disperse the alkaline mixed liquid to obtain a uniformly distributed dispersion.

[0013] In any embodiment of the present application, in the step of obtaining the dispersion, the auxiliary agent includes at least one of polyacrylate, chitosan, chitosan derivatives, alginate, polyethylenediamine, polyvinyl alcohol, acetylene glycol polyether and polyethylene glycol octylphenyl ether.

[0014] In any embodiment of the present application, in the step of obtaining a dispersion, the mass percentage ratio of the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the additive in the dispersion is (2-8):1:(0.1-1):(0.03-0.1).

[0015] In any embodiment of the present application, in the step of obtaining the dispersion, the graphite material includes at least one of artificial graphite and natural graphite.

[0016] In any embodiment of the present application, in the step of obtaining the dispersion, the sugar includes at least one of glucose, sucrose, fructose, cellulose and starch.

[0017] In any embodiment of the present application, in the step of obtaining the dispersion, the non-carbon heteroatom-containing compound includes at least one of dopamine, aniline, o-toluidine, pyridine, amino acid, polyvinylpyrrolidone, tannic acid, and citric acid.

[0018] In any embodiment of the present application, in the step of obtaining the dispersion, the pH value of the alkaline mixed solution is 8-9.

[0019] In any embodiment of the present application, in the preparation of the carbon-coated graphite precursor, the drying treatment time is 1h-48h, the drying treatment temperature is 60℃-100℃, the coking treatment time is 1h-48h, and the coking treatment temperature is 100℃-200℃.

[0020] In any embodiment of the present application, in the preparation of the carbon-coated graphite composite material, the carbonization treatment time is 60 min-240 min, and the carbonization treatment temperature is 600° C.-3500° C.

[0021] In any embodiment of the present application, the carbonization step includes a first carbonization sub-step and a second carbonization sub-step;

[0022] The first carbonization treatment temperature is 600°C-1500°C, and the time is 60min-240min;

[0023] The second carbonization treatment temperature is 1500° C.-3500° C., and the time is 60 min-240 min.

[0024] In any embodiment of the present application, in the preparation of the carbon-coated graphite composite material, the heating rate of carbonization is 2° C. / min-20° C. / min.

[0025] In a second aspect, an embodiment of the present application provides a carbon-coated graphite composite material.

[0026] A carbon-coated graphite composite material is obtained by the above-mentioned preparation method, wherein the carbon-coated graphite composite material comprises a carbon coating layer and a graphite layer, wherein the carbon coating layer is continuously and uniformly coated on the graphite layer;

[0027] The thickness of the carbon coating layer is 1nm-15nm.

[0028] In a third aspect, an embodiment of the present application provides a battery negative electrode.

[0029] A battery negative electrode comprises the carbon-coated graphite composite material as described above.

[0030] The preparation method of the carbon-coated graphite composite material, the carbon-coated graphite composite material and the battery negative electrode of the embodiment of the present application effectively prevent the merging and agglomeration of graphite particles by synergizing the carbon source and the auxiliary agent to enhance dispersion and adsorption, so that the carbon source is evenly distributed on the graphite surface to achieve uniform and complete coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solution of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0032] Figure 1 This is a scanning electron microscope photo of commercially available artificial graphite.

[0033] Figure 2 This is a transmission electron microscope photo of commercially available artificial graphite.

[0034] Figure 3 This is a scanning electron microscope photograph of the carbon-coated graphite composite material prepared in Example 1.

[0035] Figure 4 This is a transmission electron microscope photograph of the carbon-coated graphite composite material prepared in Example 1.

[0036] Figure 5 The cycle performance of soft-pack lithium-ion batteries assembled with the carbon-coated graphite composite material prepared in Example 1 and the graphite material of Comparative Example 1 as negative electrode materials respectively. DETAILED DESCRIPTION

[0037] In order to more clearly understand the above-mentioned purposes, features and advantages of the present application, the scheme of the present application will be further described below. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present application may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present application, rather than all of the embodiments.

[0039] Hereinafter, the preparation method of the carbon-coated graphite composite material, the carbon-coated graphite composite material and the battery negative electrode of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0040] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0041] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0042] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0043] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0045] Unless otherwise specified, this application adopts conventional test methods or test methods recommended by the instrument.

[0046] In the prior art, when coating an ultra-thin carbon layer for surface modification, the merging and agglomeration of graphite particles may result in uneven coating and poor coating effect.

[0047] The present application can effectively prevent the merging and agglomeration of graphite particles by synergizing the carbon source and the additive to enhance dispersion and adsorption, so that the carbon source is evenly distributed on the graphite surface, achieving low-cost ultra-thin uniform and complete coating.

[0048]

Preparation method

[0049] A method for preparing a carbon-coated graphite composite material comprises the following steps:

[0050] The alkaline mixed solution containing the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the auxiliary agent is mixed to obtain a dispersion;

[0051] Drying and coking the dispersion under preset conditions to form a carbon-coated graphite precursor;

[0052] Carbonizing the carbon-coated graphite precursor under protective gas environment conditions to obtain a carbon-coated graphite composite material;

[0053] The main carbon source for coating includes sugars;

[0054] The synergistic carbon source for coating includes a compound containing non-carbon heteroatoms;

[0055] The auxiliary agent includes a surfactant, which can cooperate with the synergistic carbon source for coating and can fully disperse the alkaline mixed liquid to obtain a uniformly distributed dispersion.

[0056] In carbon-coated graphite, on the one hand, the enhanced effect of the synergistic carbon source and the additive on dispersion and adsorption can effectively prevent the merging and agglomeration of graphite particles, making the carbon source evenly distributed on the graphite surface. On the other hand, the main carbon source and the synergistic carbon source are carbon sources different from graphite materials, so the doping and short-range structure of the carbon coating layer can be effectively regulated. On the other hand, the main carbon source and the synergistic carbon source also contain heteroatoms, and the introduction of heteroatoms can optimize the electron and ion pathways at the electrode interface.

[0057] In the step of obtaining the dispersion, vigorous stirring is required to achieve uniform mixing of the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the additive. The stirring speed may be 200 rpm-1600 rpm.

[0058] In the preparation of the carbon-coated graphite precursor, the drying method can be spray drying, freeze drying, vacuum drying or rotary evaporation drying.

[0059] In the preparation of carbon-coated graphite composite materials, the carbonization equipment is a tubular furnace, a rotary kiln or a box furnace.

[0060] In some embodiments, in the step of obtaining a dispersion, the mass percentage ratio of the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the additive in the dispersion is (2-8):1:(0.1-1):(0.03-0.1).

[0061] Optionally, the mass percentage ratio of the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the additive in the dispersion is (3-7):1:(0.3-0.8):(0.05-0.08).

[0062] Optionally, the mass percentage ratio of the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the additive in the dispersion is (4-6):1:(0.4-0.6):(0.06-0.08).

[0063] The ratio of the main carbon source for coating and the synergistic carbon source for coating can be adjusted within the above range. Without affecting the uniformity and integrity of the coating, the amount of the synergistic carbon source for coating can be reduced to save costs.

[0064] In some embodiments, the compound containing non-carbon heteroatoms includes at least one of dopamine, aniline, o-toluidine, pyridine, amino acids, polyvinylpyrrolidone, tannic acid, and citric acid. The compound containing non-carbon heteroatoms contains carbon and non-carbon heteroatoms.

[0065] In some embodiments, the graphite material includes at least one of artificial graphite and natural graphite. Among them, artificial graphite refers to a block solid material made by using carbon raw materials (petroleum coke, asphalt coke, etc.) with low impurity content as aggregates and coal tar as binders, through processes such as batching, kneading, molding, carbonization and graphitization; natural graphite refers to dense crystalline graphite, flake graphite and cryptocrystalline graphite formed by the transformation of carbon-rich organic matter under the long-term action of high temperature and high pressure geological environment.

[0066] In some embodiments, the protective gas environment condition can be achieved by filling at least one gas selected from argon, nitrogen, and neon.

[0067] In some embodiments, during the preparation of the carbon-coated graphite composite material, carbonization can be performed in stages: first, the temperature is kept at 600-1500° C. for 60 min-240 min; then the temperature is raised to 1500-3500° C. for 60 min-240 min.

[0068]

Carbon coated graphite composite material

[0069] A carbon-coated graphite composite material is obtained by the above-mentioned preparation method, wherein the carbon-coated graphite composite material comprises a carbon coating layer and a graphite layer, wherein the carbon coating layer is continuously and uniformly coated on the graphite layer;

[0070] The thickness of the carbon coating layer is 1nm-15nm.

[0071] The coating layer of the carbon-coated graphite composite material is complete and uniform. The coating layer is composed of two or more carbon materials different from graphite, which can effectively regulate the doping and short-range structure of the coating layer; heteroatoms are introduced into the coating layer, which can optimize the electronic and ion paths of the electrode interface.

[0072]

Battery

[0073] A battery negative electrode comprises the carbon-coated graphite composite material as described above.

[0074] Carbon-coated graphite composites avoid direct contact between the graphite negative electrode and the electrolyte to inhibit side reactions, significantly improving the rate performance and cycle life of the graphite negative electrode and the entire battery.

[0075] The carbon-coated graphite composite material can be used as an active material for the negative electrode material of a lithium-ion battery, and is evenly mixed with carboxymethyl cellulose CMC and styrene-butadiene rubber SBR in a certain proportion to form a slurry and coat it on a copper foil. After drying, it is rolled and die-cut to form a negative electrode sheet.

[0076] It can be assembled into button half-cells and soft-pack batteries using conventional methods.

[0077] [Example]

[0078] Example 1

[0079] Dissolve 5g of glucose and 2.5g of dopamine in 80ml of deionized water, stir until fully dissolved, and adjust the pH to 8.5. Weigh 20g of artificial graphite, add it to the above solution, and then add 3% of the total mass of glucose, dopamine and artificial graphite as an additive. Rapid mechanical stirring for 4h to obtain a dispersion. After the dispersion is evaporated and dried, it is coked at 150℃ for 3h. Move the above coked sample into a tubular furnace and carbonize it under argon atmosphere. The gas flow rate is: 100ml / min; the carbonization conditions are: heating to 600℃ at a heating rate of 2℃ / min, and keeping the temperature constant for 2h; then heating to 2000℃ at a heating rate of 5℃ / min, and keeping the temperature constant for 1h. A carbon-coated graphite composite material is obtained.

[0080] Example 2

[0081] Dissolve 5g sucrose and 1.5g tannic acid in 100ml deionized water, stir until fully dissolved, and adjust the pH to 8. Weigh 40g artificial graphite, add it to the above solution, and then add 5% polyethylenediamine of the total mass of sucrose, tannic acid and artificial graphite as an additive. Rapid mechanical stirring for 6h to obtain a dispersion. After the dispersion is vacuum dried, coke it at 140℃ for 6h. Move the above coked sample into a box furnace and carbonize it under a nitrogen atmosphere. The gas flow rate is: 100ml / min; the carbonization conditions are: heating up to 1000℃ at a heating rate of 3℃ / min, and keeping the temperature constant for 3h; then heating up to 2500℃ at a heating rate of 10℃ / min, and keeping the temperature constant for 1h. A carbon-coated graphite composite material is obtained.

[0082] Example 3

[0083] Dissolve 10g fructose and 4g citric acid in 400ml deionized water, stir until fully dissolved, and adjust the pH to 9. Weigh 50g artificial graphite, add it to the above solution, and then add 8% polyacrylate of the total mass of fructose, citric acid and artificial graphite as additives. Rapid mechanical stirring for 4h to obtain a dispersion. After the dispersion is spray-dried, coke it at 160℃ for 6h. Move the above coked sample into a rotary kiln and carbonize it under a nitrogen atmosphere. The gas flow rate is: 100ml / min; the carbonization conditions are: heating up to 1200℃ at a heating rate of 5℃ / min, and keeping the temperature constant for 4h; then heating up to 3000℃ at a heating rate of 20℃ / min, and keeping the temperature constant for 2h. A carbon-coated graphite composite material is obtained.

[0084] Example 4

[0085] Dissolve 5g of glucose and 0.5g of citric acid in 80ml of deionized water, stir until fully dissolved, and adjust the pH to 8. Weigh 30g of artificial graphite, add it to the above solution, and then add 10% of the total mass of glucose, citric acid and artificial graphite polyvinyl alcohol as an additive. Rapidly stir mechanically for 3h to obtain a dispersion. After the dispersion is freeze-dried, coke it at 140℃ for 3h. Move the above coked sample into a tubular furnace and carbonize it under argon atmosphere. The gas flow rate is: 80ml / min; the carbonization conditions are: heating up to 1100℃ at a heating rate of 3℃ / min, and keeping the temperature constant for 3h; then heating up to 2800℃ at a heating rate of 15℃ / min, and keeping the temperature constant for 2h. A carbon-coated graphite composite material is obtained.

[0086] Example 5

[0087] Dissolve 10g cellulose and 2g polyvinyl pyrrolidone in 100ml deionized water, stir until fully dissolved, and adjust the pH to 8.5. Weigh 40g artificial graphite, add it to the above solution, and then add 3% chitosan of the total mass of cellulose, polyvinyl pyrrolidone and artificial graphite as an additive. Rapid mechanical stirring for 4h to obtain a dispersion. After the dispersion is spray-dried, coke it at 150℃ for 4h. Move the above coked sample into a box furnace and carbonize it under a nitrogen atmosphere. The gas flow rate is: 90ml / min; the carbonization conditions are: heating up to 1500℃ at a heating rate of 5℃ / min, and keeping the temperature constant for 2h; then heating up to 2500℃ at a heating rate of 10℃ / min, and keeping the temperature constant for 1h. A carbon-coated graphite composite material is obtained.

[0088] Example 6

[0089] Dissolve 10g starch and 2g tannic acid in 200ml deionized water, stir until fully dissolved, and adjust the pH to 8. Weigh 50g artificial graphite, add it to the above solution, and then add 4% of the total mass of starch, tannic acid and artificial graphite as an additive. Rapid mechanical stirring for 3h to obtain a dispersion. After the dispersion is spray-dried, coke it at 150℃ for 6h. Move the above coked sample into a rotary kiln and carbonize it under a nitrogen atmosphere. The gas flow rate is: 80ml / min; the carbonization conditions are: heating up to 900℃ at a heating rate of 2℃ / min, and keeping the temperature constant for 4h; then heating up to 3500℃ at a heating rate of 20℃ / min, and keeping the temperature constant for 1h. A carbon-coated graphite composite material is obtained.

[0090] Example 7

[0091] Dissolve 8g fructose and 1g dopamine in 300ml deionized water, stir until fully dissolved, and adjust the pH to 9. Weigh 40g artificial graphite, add it to the above solution, and then add 10% alginate of the total mass of fructose, dopamine and artificial graphite as an additive. Rapid mechanical stirring for 4h to obtain a dispersion. After the dispersion is freeze-dried, coke it at 150℃ for 4h. Move the above coked sample into a box furnace and carbonize it under a nitrogen atmosphere. The gas flow rate is: 150ml / min; the carbonization conditions are: heating up to 1300℃ at a heating rate of 4℃ / min, and keeping the temperature constant for 2h; then heating up to 2800℃ at a heating rate of 15℃ / min, and keeping the temperature constant for 2h. A carbon-coated graphite composite material is obtained.

[0092] Comparative Example 1

[0093] Weigh an appropriate amount of artificial graphite without any treatment.

[0094] Comparative Example 2

[0095] Dissolve 5g of glucose in 80ml of deionized water, stir until fully dissolved, and adjust the pH to 8.5. Weigh 20g of artificial graphite, add it to the above solution, and then add 3% of the total mass of glucose and artificial graphite polyethylenediamine as an additive. Rapid mechanical stirring for 4h to obtain a dispersion. After the dispersion is dried by rotary evaporation, it is coked at 150℃ for 3h. Move the above coked sample into a tubular furnace and carbonize it under argon atmosphere. The gas flow rate is: 100ml / min, and the carbonization conditions are: heating to 600℃ at a heating rate of 2℃ / min, and keeping the temperature constant for 2h; then heating to 2000℃ at a heating rate of 5℃ / min, and keeping the temperature constant for 1h. A carbon-coated graphite composite material is obtained.

[0096] Comparative Example 3

[0097] Dissolve 2.5g dopamine in 80ml deionized water, stir until fully dissolved, and adjust the pH to 8.5. Weigh 20g artificial graphite, add it to the above solution, and then add 3% polyethylenediamine of the total mass of dopamine and artificial graphite as an additive. Rapid mechanical stirring for 4h to obtain a dispersion. After the dispersion is dried by rotary evaporation, it is coked at 150℃ for 3h. Move the above coked sample into a tubular furnace and carbonize it under argon atmosphere. The gas flow rate is: 100ml / min, and the carbonization conditions are: heating to 600℃ at a heating rate of 2℃ / min, and keeping the temperature constant for 2h; then heating to 2000℃ at a heating rate of 5℃ / min, and keeping the temperature constant for 1h. A carbon-coated graphite composite material is obtained.

[0098] Comparative Example 4

[0099] Dissolve 5g of glucose and 2.5g of dopamine in 80ml of deionized water, stir until fully dissolved, and adjust the pH to 8.5. Weigh 20g of artificial graphite, add it to the above solution, and stir it mechanically for 4h to obtain a dispersion. After the dispersion is dried by rotary evaporation, it is coked at 150℃ for 3h. Move the coked sample into a tubular furnace and carbonize it under an argon atmosphere. The gas flow rate is: 100ml / min, and the carbonization conditions are: heat up to 600℃ at a rate of 2℃ / min, and keep the temperature constant for 2h; then heat up to 2000℃ at a rate of 5℃ / min, and keep the temperature constant for 1h. A carbon-coated graphite composite material is obtained.

[0100] The materials obtained in the above embodiments and comparative examples are used as active substances of negative electrode materials of lithium-ion batteries, and are evenly mixed with carboxymethyl cellulose CMC and styrene-butadiene rubber SBR in a ratio of 9:0.5:0.5 to make a slurry and coat it on copper foil. The prepared pole piece is vacuum dried at 90°C for 12 hours, and then rolled and die-cut after drying.

[0101] The button half-cell was assembled by conventional method to test its first coulombic efficiency and capacity; the soft-pack battery was assembled with NCM811 as the positive electrode to test its cycle performance.

[0102] Button battery test: Under normal temperature conditions, 0.1C constant current charge and discharge, voltage range 0.001V-1.5V, test and record its first charge and discharge capacity and efficiency, the test results are shown in Table 1.

[0103] Soft pack battery test: Under normal temperature conditions, first use 0.1C to charge and discharge for 2 cycles, then 0.5C charge and discharge cycle to test its cycle performance. The test results are as follows: Figure 1-Figure 5 shown.

[0104] Table 1. Performance of button-type half-cells corresponding to the negative electrodes prepared in each group of examples and comparative examples

[0105]

[0106]

[0107] Figure 2 and Figure 4 Comparison shows that the carbon-coated graphite composite material forms a uniform core-shell structure, and the coated carbon layer is about 6nm. Figure 5 The battery test performance shows that the present application improves the first coulombic efficiency and cycle performance by constructing an ultra-thin carbon layer tightly wrapping the graphite negative electrode to avoid direct contact between the graphite negative electrode and the electrolyte to inhibit side reactions.

Claims

1. A method for preparing a carbon-coated graphite composite material, characterized in that: include: The alkaline mixed solution containing the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the auxiliary agent is mixed to obtain a dispersion; Drying and coking the dispersion under preset conditions to form a carbon-coated graphite precursor; Carbonizing the carbon-coated graphite precursor under protective gas environment conditions to obtain a carbon-coated graphite composite material; The main carbon source for coating includes sugars; The synergistic carbon source for coating includes a compound containing non-carbon heteroatoms; The auxiliary agent includes a surfactant, which can cooperate with the synergistic carbon source for coating and can fully disperse the alkaline mixed liquid to obtain a uniformly distributed dispersion.

2. The preparation method according to claim 1, characterized in that: In the step of obtaining the dispersion, the auxiliary agent includes at least one of polyacrylate, chitosan, chitosan derivatives, alginate, polyethylenediamine, polyvinyl alcohol, acetylene glycol polyether and polyethylene glycol octylphenyl ether.

3. The preparation method according to claim 1, characterized in that: In the step of obtaining the dispersion, the mass percentage ratio of the graphite material, the main carbon source for coating, the synergistic carbon source for coating and the auxiliary agent in the dispersion is (2-8):1:(0.1-1):(0.03-0.1).

4. The preparation method according to any one of claims 1 to 3, characterized in that In the step of obtaining the dispersion, the graphite material includes at least one of artificial graphite and natural graphite.

5. The preparation method according to any one of claims 1 to 3, characterized in that: In the step of obtaining the dispersion, the sugar includes at least one of glucose, sucrose, fructose, cellulose and starch.

6. The preparation method according to any one of claims 1 to 3, characterized in that: In the step of obtaining the dispersion, the compound containing non-carbon heteroatoms includes at least one of dopamine, aniline, o-toluidine, pyridine, amino acid, polyvinyl pyrrolidone, tannic acid and citric acid.

7. The preparation method according to claim 1, characterized in that: In the step of obtaining the dispersion, the pH value of the alkaline mixed solution is 8-9.

8. The preparation method according to claim 1, characterized in that: In the step of forming a carbon-coated graphite precursor, The drying treatment time is 1h-48h, the drying treatment temperature is 60℃-100℃, the coking treatment time is 1h-48h, and the coking treatment temperature is 100℃-200℃; And / or, in the step of obtaining the carbon-coated graphite composite material, the carbonization treatment time is 60 min-240 min, and the carbonization treatment temperature is 600° C.-3500° C.; Preferably, the carbonization step includes a first carbonization sub-step and a second carbonization sub-step; The first carbonization treatment temperature is 600°C-1500°C, and the time is 60min-240min; The second carbonization treatment temperature is 1500°C-3500°C, and the time is 60min-240min; And / or, in the obtained carbon-coated graphite composite material, the heating rate of the carbonization treatment is 2°C / min-20°C / min.

9. A carbon-coated graphite composite material, characterized in that: The method according to any one of claims 1 to 8 is used to prepare the carbon-coated graphite composite material, wherein the carbon-coated graphite composite material comprises a carbon coating layer and a graphite layer, and the carbon coating layer is continuously and uniformly coated on the graphite layer; The thickness of the carbon coating layer is 1 nm-15 nm.

10. A negative electrode of a battery, characterized in that: Comprising the carbon-coated graphite composite material as claimed in claim 9.

Citation Information

Patent Citations

  • Silicon-carbon composite negative electrode material for lithium ion battery and preparation method thereof

    CN103474667A

  • Core-shell structure multi-component composite material, preparation method thereof and a lithium ion battery comprising the multi-component composite material

    CN108832092A

  • Spherical core-shell structure mixed graphite @ hard carbon composite material as well as preparation method and application thereof

    CN109616638A

  • Hard carbon-coated graphite negative electrode material, lithium ion battery, and preparation method and application thereof

    CN111244401A

  • Carbon-coated graphite negative electrode material, preparation method thereof and battery

    CN115986091A

Cited By

  • Graphite crucible and preparation method and application thereof

    CN119874408A

  • Modified oxidized chitosan bio-based phenolic resin, preparation and application thereof, negative electrode and battery

    CN121378620A